Innovative trifocal (quadrifocal) presbyopia-correcting IOLs: 1-year outcomes from an international multicenter study. Issue 8 (August 2020) - Kohnen, Thomas; Marchini, Giorgio; Alfonso, Jose F.; Bala, Chandra; Cochener, Beatrice; Martinez, Aldo; Carreño, Edgardo
Abstract : Trifocal IOLs provided an excellent safety profile with satisfactory patient outcomes for UDVA, DCIVA, and UNVA. Defocus curve demonstrated 20/25 Snellen or better visual acuity at near to intermediate distance. Abstract : Purpose: To evaluate visual acuity (VA) and safety of the new AcrySof IQ PanOptix presbyopia-correcting IOL at 12 months postimplantation. Setting: Seventeen sites in Europe, Australia, and South America. Design: Prospective, single-arm, nonmasked, nonrandomized study. Methods: Of 167 patients enrolled, 149 received study IOLs in both eyes; 145 completed the study. Binocular uncorrected distance VA (UDVA; 4 m), monocular corrected distance VA (CDVA), binocular distance-corrected intermediate VA (DCIVA; 60 cm and 80 cm), binocular uncorrected near VA (UNVA; 40 cm), and binocular defocus curves were evaluated. Safety was assessed by monitoring adverse events (AEs). Results: Of 149 patients, 92 patients (62%) were women and 139 patients (93%) were white; mean ± SD age was 68.9 ± 9.3 years. At 12 months, mean binocular UDVA was 0.02 ± 0.11 logarithm of the minimum angle of resolution (logMAR); monocular CDVA was 0.01 ± 0.13 logMAR (first eye) and 0.01 ± 0.10 logMAR (second eye); binocular DCIVA was 0.04 ± 0.12 logMAR and 0.08 ± 0.14 logMAR at 60 cm and 80 cm, respectively; and binocular UNVA was 0.07 ± 0.11 logMAR. At 6 months, mean binocular defocus curve VA (0.00 diopter [D] to −3.00 D) ranged from −0.04 to 0.13 logMAR. Binocular VA at distance (0.00 D), intermediate (−1.50 D), and near (−2.50 D) was −0.04 ± 0.11 logMAR, 0.07 ± 0.13 logMAR, and 0.07 ± 0.13 logMAR, respectively. Serious ocular AE rates were 1.4% or less in first and second eyes. Posterior capsulotomy rates were 3.4% (first eye) and 2.7% (second eye). Conclusions: The study IOL provided good VA outcomes. Defocus curve showed VA of 20/25 Snellen or better from near to intermediate distance. Rates of serious and nonserious AEs were low.